Scottish Latin authors in print up to 1700 : a short-title list - Green, R. P. H.; Burton, Philip (Philip Hugh); Ford, D. J. (Deborah J.) (Supplementa humanistica Lovaniensia ;, 2012)
The work of the Latin writers of Scotland has suffered a neglect which its variety, copiousness, and intrinsic interest do not deserve. Their importance, and the importance of Latin as a literary language, is beginning to be recognized by scholars. Researchers from the universities of Glasgow and St. Andrews have now prepared the first-ever bibliography of Scottish Latin in print - unique both in its focus on the many works written in Latin and in the way in which Scottish writers are specifically targeted. Covering the years c. 1480-1700, this new reference tool carefully catalogues the work of some 500 writers, in both prose and verse. Thousands of works are named in a clear and original format, with their titles not so truncated as to be obscure (as sometimes happens in English 'short-title' catalogues). The editors take advantage of recent research, and many poetic works hitherto unknown or ignored are referenced.